Influence of chronic training workload on the hematological profile: a pilot study in sedentary people, amateur and professional cyclists: Hematological profile in athletes - Lippi, Giuseppe; Sanchis-Gomar, Fabian (Acta Biomedica Atenei Parmensis, 2020)
Background and aim: The assessment of hematological profile requires to identify possible sources of biological variability, including exercise-related variations. This study was hence aimed to evaluate hematological profile variations in amateur and professional athletes, and establish their possible dependence on cumulative training volume. Materials and Methods: The study population consisted of 59 sedentary male subjects, 78 amateur and 80 professional male cyclists, in whom a large number of hematological variables were measured at rest. Results: Red blood cell (RBC) count and hemoglobin were decreased in the two athlete cohorts compared to sedentary subjects, but did not differ between amateur and professional cyclists. Hematocrit was gradually and significantly decreased in parallel with cumulative training volume. Amateur cyclists displayed higher mean corpuscular volume (MCV) and lower mean corpuscular hemoglobin concentration (MCHC) values than sedentary subjects and professional cyclists, whilst mean corpuscular hemoglobin (MCH) was higher in professional cyclists. The reticulocyte count and soluble transferrin receptor (sTFR) values were similar across all groups. Serum ferritin was higher in professional cyclists than in the other two groups, whilst transferrin gradually decreased from sedentary group to the two cohorts of amateur and professional cyclists. In univariate analysis, cumulative training volume was inversely associated with age, body mass index (BMI), RBC count, hematocrit, hemoglobin and transferrin, whilst a positive association was found with ferritin. In multivariate analysis, BMI, RBC count and ferritin remained significantly associated with training volume. Conclusions: These results show that the volume of endurance training may affect some hematological variables.